Fungal Fermentation of Distillers Dried Grains with Solubles (DDGS) with Trichoderma reesei and Soybean Hull - Gallant, Ethan T; Hu, Bo; Sun, Xiao (My University, 2021)
The main issue with utilizing DDGS as feeding ingredients for mono-gastric animals such as swine is its high concentration of fiber, phytate, and low levels of important amino acids, such as lysine, threonine, and methionine. To improve the utility of DDGS, the impact of solid-state fermentation on DDGS with the fungal strains, Trichoderma reesei (TR), Aspergillus oryzae (AO), and Mucor indicus (MI) was investigated. Results from experiments show fermenting DDGS and soybean hull with Trichoderma reesei and urea as the substrate for six days provides the best improvement in the amino acid profile and the most phytate and structural carbohydrate reduction. Fermentation DDGS and soybean hull with TR and urea produced a 56.84% increase in lysine, threonine, and methionine compared to the control samples analyzed. With TR and urea, phytate levels were reduced by 23.41%. Additionally, TR reduced the total carbohydrates in DDGS by 7.19% compared to TR and MI. TR and MI both produced the most amino acids with urea as the nitrogen source, while AO produced the most amino acids with ammonium nitrate as the nitrogen source. These results show the solid-state fermentation of DDGS and soybean hull with Trichoderma reesei and urea provide a significant improvement in the overall usefulness of the feed to livestock.
Keywords: Agriculture; Fermentation